2014
DOI: 10.1111/plb.12199
|View full text |Cite
|
Sign up to set email alerts
|

Pollen competition between two sympatric Orchis species (Orchidaceae): the overtaking of conspecific of heterospecific pollen as a reproductive barrier

Abstract: The frequency of hybrid formation in angiosperms depends on how and when heterospecific pollen is transferred to the stigma, and on the success of that heterospecific pollen at fertilising ovules. We applied pollen mixtures to stigmas to determine how pollen interactions affect siring success and the frequency of hybrid formation between two species of Mediterranean deceptive orchid. Plants of Orchis italica and O. anthropophora were pollinated with conspecific and heterospecific pollen (first conspecific poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Several studies have examined how post-pollination processes influence the degree of assortative mating and the strength of reproductive barriers between species (e.g., Rahmé et al, 2009;Widmer et al, 2009;Ostevik et al, 2016). Similar to the results of our study, conspecific pollen performance is higher than heterospecific performance in Ipomopsis arizonica (Wolf et al, 2001), sympatric Orchis species (Luca et al, 2015), Silene latifolia (Rahmé et al, 2009;Montgomery et al, 2010), Arabidopsis thaliana accession Columbia (Swanson et al, 2016), and some species of the Erica genus (Coetzee et al, 2020). In particular, Rahmé and colleagues (2009) found that when mixing equal proportions of pollen from compatible Silene latifolia and S. dioica species, the differential success of conspecific vs. heterospecific pollen revealed an asymmetric post-zygotic reproductive barrier toward hybrid formation.…”
Section: The Timing Of Pollination Can Reduce Assortative Mating and ...supporting
confidence: 87%
“…Several studies have examined how post-pollination processes influence the degree of assortative mating and the strength of reproductive barriers between species (e.g., Rahmé et al, 2009;Widmer et al, 2009;Ostevik et al, 2016). Similar to the results of our study, conspecific pollen performance is higher than heterospecific performance in Ipomopsis arizonica (Wolf et al, 2001), sympatric Orchis species (Luca et al, 2015), Silene latifolia (Rahmé et al, 2009;Montgomery et al, 2010), Arabidopsis thaliana accession Columbia (Swanson et al, 2016), and some species of the Erica genus (Coetzee et al, 2020). In particular, Rahmé and colleagues (2009) found that when mixing equal proportions of pollen from compatible Silene latifolia and S. dioica species, the differential success of conspecific vs. heterospecific pollen revealed an asymmetric post-zygotic reproductive barrier toward hybrid formation.…”
Section: The Timing Of Pollination Can Reduce Assortative Mating and ...supporting
confidence: 87%
“…; Luca et al . ) and Narcissus (Marques et al . , ), which reveals that our knowledge about the role of isolation barriers is poorly understood for most of the hybridising Mediterranean groups.…”
Section: Hybridisation and Polyploidy In The Mediterranean Regionmentioning
confidence: 99%
“…Generally, food‐deceptive orchid species (which exhibit weaker pollinator specificity than sexual‐deceptive species) rely on post‐mating isolation, such as hybrid sterility, as a reproductive barrier to avoid hybridization (Scopece et al 2007; Cozzolino & Scopece 2008). However, competition between conspecific and heterospecific pollen can operate as a post‐pollination pre‐zygotic barrier that limits the frequency of hybrid formation in nature (Luca et al 2015).…”
Section: Introductionmentioning
confidence: 99%